Social factors that contribute to financial constraints among Youth in Petaling District, Selangor / Nur Zafirah Zamri and Radduan Yusof - Zamri, Nur Zafirah; Yusof, Radduan (2021)
Khairudin Murad and Shahnon Mohd Salleh (2014) defined youth as the period between adolescence and adulthood. According to the Asian Institute of Finance (AIF) (2015), youth become vulnerable to their surrounding environment at this phase when they are busy exploring their self-identities and foundations of life. What people are surrounded by has a strong influence on their way of life. Compared to earlier generations, youth have more significant financial risk due to the rising complexity and diversity of financial goods and marketplaces (The Star, 2015). Generation Y was born and raised in a flourishing, expanding economy. This generation is noted for having more alternatives and a higher quality of life than previous generations (Warren, 2003). The need to keep up with the current trend is centered on meeting social standards and "fitting in" with their peers, which is worsened by their borrowing mentality (Faizal et al., 2015). According to Urbis et al. (2008), the "own now, pay later" credit attitude is becoming more prevalent among young people. When faced with a situation where they desired something but cannot afford it, 80 percent of respondents found a way to get it without even thinking about it, according to the study. Money has become a "must" in the twenty-first century, as rapid advancement has made it a must to continue existing effectively. Only thoughtful financial preparation can enable one to enjoy life while also avoiding any financial difficulties. However, it is difficult for today's youth to maintain complete control over their spending and saving habits. The main reason for this scenario is due to the evolvement of globalization. It makes technology and social media platforms appear to be a pressure source on young people. It influenced young people to spend money that they did not have and spend beyond their means to live up to the "digital society" standards (Azira Abdul Adzis et al., 2017).